Analisis Praktik Pengelolaan Keuangan Dan Dampaknya Terhadap Stabilitas Usaha (Studi Kasus UMKM Toko Fitri) - Dhita Rahmadhani; Dianing Widya Kusumastuti (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to analyze financial management practices and their impact on business stability in the MSME Toko Fitri, located in Karanganyar Regency. A descriptive qualitative approach was employed, with data collected through interviews, observations, and documentation. The results reveal that financial management is carried out traditionally without a formal accounting system, yet the business remains stable. The owner applies cash separation between personal and business finances, cash-only transactions, and inventory control based on turnover. These findings indicate that simple and experience-based approaches can adaptively sustain microenterprise continuity. Theoretically, this research reinforces the resource-based theory emphasizing the importance of internal capability in creating competitive advantage. Practically, the study highlights the urgency of implementing simple bookkeeping systems for MSMEs to enhance financial efficiency and transparency.